Correlation and Survival Analysis of Distant Metastasis Site and Prognosis in Patients With Hepatocellular Carcinoma - Zhan, Hao; Zhao, Xue; Lu, Zhaoxue; Yao, Yuanhu; Zhang, Xuguang (Frontiers in Oncology, 2021)
Purpose: To investigate the prognostic factors and survival analysis of patients with hepatocellular carcinoma（HCC） with distant metastasis. Methods: The clinical data of 3,126 patients with distant metastasis of HCC from 2010 to 2015 were extracted from SEER database, and the correlation between the location of distant metastasis of HCC and prognosis was retrospectively analyzed. Patients were grouped according to different metastatic sites. The clinical characteristics of each group were compared by chi-square test, the survival curve was drawn by Kaplan-Meier method, Log-rank test was used for univariate analysis, and Cox regression for multivariate analysis. And use propensity score matching (PSM) to reduce differences in baseline characteristics. Results: Before PSM, the prognosis of patients with HCC with lung metastasis is worse than that of patients without lung metastasis. And there was no statistically significant difference with or without bone metastases .Patients with one type of organ metastasis had better prognosis than those with multiple organ metastasis. Among patients with organ metastasis, bone metastasis has a better prognosis than patients with lung metastasis. After PSM, patients with HCC with bone metastases had a worse prognosis than those without bone metastases (P＜0.05). Univariate analysis showed that the degree of tumor differentiation, T stage, N stage, primary tumor and metastatic surgery, radiotherapy and chemotherapy, tumor size, single organ metastasis, the number of metastatic organs, and the combination of metastatic organs were related to the prognosis of patients with distant metastasis of HCC (P < 0.05). Multiariate analysis showed that age ≥52 years old, male, low degree of tumor differentiation, N1 stage, no primary surgery, no chemoradiotherapy, tumor size > 6cm, and multi-organ metastasis were independent influencing factors for poor prognosis in patients with metastatic HCC. Conclusion: The lung is the most common site of distant metastasis of HCC. Single organ metastasis has better prognosis than multiple organ metastasis. Age ≥52 years old, male, low degree of tumor differentiation, N1 stage, no primary surgery, no chemoradiotherapy, tumor size > 6cm, and multi-organ metastasis were independent influencing factors for poor overall survival and cancer-specific survival prognosis in patients with metastatic HCC.